The Effect of Chisel Sharpening and Without Chisel Sharpening on the Surface Roughness of the Piston Waste Casting Material - Betan, Agustinus Deka (Universitas Muhammadiyah Metro, 2023)
This research begins with the casting process of motorcycle piston waste and then continues with the turning process on conventional lathes. The purpose of this machining process is to identify the quality of the surface roughness of the turned casting product. The surface roughness quality of the turning product to be applied must show high precision and not experience significant surface defects. To get the surface quality, there are many machining variables that need to be considered, one of which is the use of lathe chisels. The turning tool becomes an important component during the turning process to form various forms of products produced through the mediation of rotary motion and tool motion resulting in large and small friction. This friction that occurs will depend on the sharpness of the chisel itself. The problem studied is the use of sharpened and non-sharpened chisels in terms of product surface roughness during the turning process. In addition, this study will vary the variable thickness of the feed which varies 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm to be a factor in finding out the quality of turning products. While the spindle rotation of the lathe used is 240 rpm, 350 rpm, 430 rpm. From the experiments on turning the casting product, it was found that the lowest surface roughness quality was obtained with the N6 sharpened chisel of 1.13 mm while the N6 unsharpened chisel was 1.19 mm.Keywords: lathe chisel, casting, piston waste, turning, surface roughness value.